Experiences of severe childhood maltreatment, depression, anxiety and alcohol abuse among adults in Finland - Rehan W; Antfolk J; Johansson A; Jern P; Santtila P (PUBLIC LIBRARY SCIENCE, 2022)
Childhood maltreatment increases the risk of subsequent depression, anxiety and alcohol abuse, but the rate of resilient victims is unknown. Here, we investigated the rate of victims that do not suffer from clinical levels of these problems after severe maltreatment in a population-based sample of 10980 adult participants. Compared to men, women reported more severe emotional and sexual abuse, as well as more severe emotional neglect. For both genders, severe emotional abuse (OR = 3.80 [2.22, 6.52]); severe physical abuse (OR = 3.97 [1.72, 9.16]); severe emotional neglect (OR = 3.36 [1.73, 6.54]); and severe physical neglect (OR = 11.90 [2.66, 53.22]) were associated with depression and anxiety while only severe physical abuse (OR = 3.40 [1.28, 9.03]) was associated with alcohol abuse. Looking at men and women separately, severe emotional abuse (OR = 6.05 [1.62, 22.60] in men; OR = 3.74 [2.06, 6.81] in women) and severe physical abuse (OR = 6.05 [1.62, 22.60] in men; OR = 3.03 [0.99, 9.33] in women) were associated with clinical levels of depression and anxiety. In addition, in women, severe sexual abuse (OR = 2.40 [1.10, 5.21]), emotional neglect (OR = 4.78 [2.40, 9.56]), and severe physical neglect (OR = 9.86 [1.99, 48.93]) were associated with clinical levels of depression and anxiety. Severe emotional abuse in men (OR = 3.86 [0.96, 15.48]) and severe physical abuse in women (OR = 5.18 [1.48, 18.12]) were associated with alcohol abuse. Concerning resilience, the majority of severely maltreated participants did not report clinically significant levels of depression or anxiety (72%), or alcohol abuse (93%) in adulthood. Although the majority of severely abused or neglected individuals did not show clinical levels of depression, anxiety or alcohol use, severe childhood maltreatment increased the risk for showing clinical levels of psychopathology in adulthood.